On the philosophy and logic of human action: A Neo-Austrian contribution to the methodology of the social sciences - Oliva Cordoba, Michael (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2024)
Philosophical action theory seems to be in pretty good shape. The same may not be true for the study of human action in economics. Famous is the rant that the study of human action in economics gives reason to tremble for the reputation of the subject. But how does this come about? Since economic action is about action, the broader study must surely have a strong impact on the more specific field. The paper sets out, from the ground up, how an essential concept in economic theory–the concept of competition–can fundamentally benefit from insights derived exclusively from analytical action theory broadly conceived. In doing so, the paper delivers on an old Austrian promise: it is sometimes claimed that Austrian economists understand competition better than most economists. This may be a bold claim, since Austrian economists have neither traced the understanding of subjectivity to its very origin (the theory of intentionality), nor have they traced their sympathy for methodological individualism in relation to market processes to its very ground (the theory of (human) action). This paper aims to fill this gap. Moreover, by grounding an Austrian view of competition in analytic action theory, it succeeds in avoiding the serious problems of the dominant equilibrium approach. By explaining competition as rivalry, the paper draws on the philosophy and logic of human action to bring the (economic) agent back into play. In this way, a case is made for an integrated view of Austrian theory as an amalgam of Austrian economics and analytic action theory.